Clinical impact of multi-parameter continuous non-invasive monitoring in hospital wards: a systematic review and meta-analysis - Sun,L; Joshi,M; Khan,SN; Ashrafian,H; Darzi,A (Journal of the Royal Society of Medicine, 2020)
ObjectiveDelayed response to clinical deterioration as a result of intermittent vital sign monitoring is a cause of preventable morbidity and mortality. This review focuses on the clinical impact of multi-parameter continuous non-invasive monitoring of vital signs (CoNiM) in non-intensive care unit patients.DesignSystematic review and meta-analysis of primary studies. Embase, MEDLINE, HMIC, PsycINFO and Cochrane were searched from April 1964 to 18 June 2019 with no language restriction.SettingThe search was limited to hospitalised, non-intensive care unit adult patients who had two or more vital signs continuously monitored.ParticipantsAll primary studies that evaluated the clinical impact of using multi-parameter CoNiM in adult hospital wards outside of the intensive care unit.Main outcome measuresClinical impact of multi-parameter CoNiM.